2018
DOI: 10.1200/jco.2018.36.4_suppl.587
|View full text |Cite
|
Sign up to set email alerts
|

Estimating 1- and 5-year relative survival trends in colorectal cancer (CRC) in the United States: 2004 to 2014.

Abstract: 587 Background: Patient survival is impacted by several factors, one of which is stage at diagnosis. From 1976 to 2014, CRC death rate in the United States (US) declined by 51%. This retrospective study was conducted using US Surveillance, Epidemiology and End Results (SEER) data to evaluate 1- and 5-year relative survival for patients with CRC by American Joint Committee on Cancer (AJCC) stage, age and sex at diagnosis. Methods: The study included adults (age ≥20 years) in the SEER-18 registry diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 0 publications
4
36
0
Order By: Relevance
“…However, age may work as a confounder [15]. Specifically, previous studies in colorectal cancer patients showed that survival is lower in patients aged 65 years or more, compared with patients younger than 65 years [16][17][18]. A stratified analysis of our study population produced a similar result (Table 3).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, age may work as a confounder [15]. Specifically, previous studies in colorectal cancer patients showed that survival is lower in patients aged 65 years or more, compared with patients younger than 65 years [16][17][18]. A stratified analysis of our study population produced a similar result (Table 3).…”
Section: Discussionsupporting
confidence: 73%
“…From the above findings, we can conclude that older patients in the OCS group and a higher number of deaths were not connected to malignant neoplasm in the OCS group, which surely increased the mortality in this group. Overall, the five-year survival of the enrolled patients was comparable with survival of similar patients (we excluded patients with stage IV disease) in other, larger studies researching colorectal cancer mortality [16,17].…”
Section: Discussionmentioning
confidence: 67%
“…The AJCC TNM staging system and age are well‐known important prognostic factors . In the multivariate analysis conducted in the present study, TNM stage and age remained significantly associated with survival besides the FunPGS in the meta‐discovery and TCGA cohorts, indicating the independent and complementary value of TNM stage and age.…”
Section: Resultssupporting
confidence: 58%
“…Despite the recent advances in early detection and introduction of new therapeutic means, such as neoadjuvant chemoradiation, the five-year survival rates for stage IV CRC are as low as 14.4% for patients aged <65 years and 7.4% for patients aged 65 years [44]. Recurrence rates for two-and five-year follow-up also remain high, ranging from 15 to 30% [45,46].…”
Section: Monitoring Prognosis After Diagnosis and Treatmentmentioning
confidence: 99%